Modern possibilities of the diagnosing of primary hyperparathyroidism - Marina E. Boriskova; Polina A. Pankova; Lina A. Khamid; Mikhail A. Bykov; Daria V. Zuykevich; Kristina V. Valiakhmedova; Zalina M. Ulimbasheva; Karina A. Pogosy0an; Tatiana L. Karonova; Daria V. Ryzhkova (Consilium Medicum)
Background. Currently, the most common method of preoperative imaging of affected parathyroid glands (PTG) is a combination of scintigraphy with technetium [99mTc] sestamibi and neck ultrasound (with a sensitivity of 81–95%). In some cases, such as multiple PTG lesions, their ectopic location, multiple nodular thyroid lesions, and their hyperfunction or inflammation, standard imaging methods may show negative or contradictory results, which requires the use of 2nd-line diagnostic studies. One is positron emission tomography combined with computed tomography (PET/CT) with 11C-choline.